Risk disclosure analysis in the corporate Governance Annual Report using fuzzy-set qualitative comparative analysis - Pedro Carmona; Cristina de Fuentes; Carmen Ruiz (RAE: Revista de Administração de Empresas, 2016)
This paper explores the necessary and sufficient conditions of good Corporate Governance practices for high risk disclosure by firms in their Corporate Governance Annual Report. Additionally, we explore whether those recipes have changed during the financial crisis. With a sample of 271 Spanish listed companies, we applied fuzzy-set qualitative comparative analysis to a database of financial and non-financial data. We report that Board of Directors independence, size, level of activity and gender diversity, CEO duality, Audit Committee independence, being audited by the Big Four auditing firms and the presence of institutional investors are associated with high risk disclosure. The conditions included in almost every combination are the presence of institutional investors and being audited by the Big Four. We found similar combinations for 2006 and 2012, while the analysis for 2009 showed the lowest number of causal configurations.